Indeks Keluarga Sehat Wilayah Pengalaman Belajar Lapangan Program Studi Kesehatan Masyarakat UIN Alauddin Makassar - Lilis Widiastuty; Ranti Ekasari (Public Health Department, Universitas Islam Negeri Alauddin Makassar, 2022)
Health is an investment in the economic development of a nation and as the efforts to reduce poverty. Indonesia's health development efforts are carried out by all components of the nation with the aim of fostering awareness, desire and ability to live a healthy life for everyone, in order to realize the highest degree of health. To achieve the development priorities in the health sector for 2015-2019, the Healthy Indonesia Program will be implemented by empowering all potentials and assets owned by the Indonesian nation, both from the central, provincial, district/city governments, and the community. Health development efforts begin with the smallest unit, namely the family. This study aimed to determine the achievement of the healthy family index in the Learning Experience area of the Public Health Study Program at UIN Alauddin Makassar. This research was an observational study with descriptive analysis. The research population was all families who live in Limapoccoe Village, Cenrana District, Maros Regency. The samples were 232 households in Mappasaile hamlet and 118 in Kaluku hamlet. The results showed that the healthy family index in Mappasaile Hamlet was 0.219 (unhealthy family) and Kaluku Hamlet was 0.169 (unhealthy family), thus the healthy family index in Limapoccoe Village was 0.202 (unhealthy family). The government is suggested to make policies for supporting the implementation of the 12 indicators of healthy families such as recipients of cash assistance not having family members who smoke, and more intensive officers going into the field to educate the public to implement the 12 indicators of healthy families. Keywords: healthy family index, health, learning service area